Poly(methyl methacrylate) grafting onto stainless steel surfaces: application to drug-eluting stents - Shaulov, Yulia; Okner, Regina; Levi, Yair; Tal, Noam; Gutkin, Vitaly; Mandler, Daniel; Domb, Abraham J. (ACS Appl Mater InterfacesACS applied materials & interfaces, 2009)
Drug-eluting stents (DESs) have been associated with adverse clinical effects. Moreover, recent publications have shown that the coating of DESs suffers from defects. The purpose of this contribution is to examine a three-step process for surface modification as a means of improving the durability of DESs. In the first step, 4-(2-bromoethyl)benzenediazonium tetrafluoroborate was electrografted onto a stainless steel (SS) stent. X-ray photoelectron spectroscopy (XPS) of the modified stent confirmed the formation of the organic layer. In the second step, methyl methacrylate was polymerized onto the grafted surface by atom-transfer radical polymerization. XPS, electrochemical impedance spectroscopy, and contact-angle measurements were used to characterize the polymer brushes. The last step involved spray-coating of the stent with a drug-in-polymer matrix [poly(n-butyl methacrylate)/poly(ethylene-co-vinyl acetate) + paclitaxel]. Scanning electron microscopy confirmed the considerably improved durability of the drug-in-polymer matrix. Bare controls showed greater cracking and delamination of the coating than did the two-step modified stents after incubation under physiological (37 degrees C) and accelerated (60 degrees C) conditions. Finally, paclitaxel controlled release from the modified SS DESs was moderate compared with that of nontreated samples. In conclusion, the proposed method significantly improves the durability of drug-in-polymer matrixes on a SS DESs.[on SciFinder (R)]
MEDLINE AN 2010227904(Journal; Article; (JOURNAL ARTICLE); (RESEARCH SUPPORT, NON-U.S. GOV’T))